Comparison of Transperitoneal and Retroperitoneal Robotic Partial Nephrectomy for Patients With Complete Upper Pole Renal Tumors - Gu, Liangyou; Zhao, Wenlei; Xu, Junnan; Wang, Baojun; Cheng, Qiang; Shen, Donglai; Xuan, Yundong; Zhao, Xupeng; Li, Hongzhao; Ma, Xin; Zhang, Xu (Frontiers in Oncology, 2022)
Objectives: We compared the outcomes of transperitoneal robotic partial nephrectomy (TRPN) and retroperitoneal robotic partial nephrectomy (RRPN) for completely upper pole renal masses [1 point for the ‘L’ component of the R.E.N.A.L. scoring system]. Material and methods: We retrospectively reviewed patients who underwent either TRPN or RRPN from 2013 to 2016. Baseline demographics, perioperative, functional, and oncological results were compared. Multivariable analysis was performed to identify factors related to pentafecta achievement [ischemia time ≤ 25 minutes, negative margin, perioperative complication free, glomerular filtration rate (eGFR) preservation >90%, and no chronic kidney disease upstaging]. Results: No significant differences between TRPN vs. RRPN were noted for operating time (110 vs. 114 min, p = 0.870), renal artery clamping time (19 vs. 18 min, p = 0.248), rate of positive margins (0.0 vs.3.3%, p = 0.502), postoperative complication rates (25.0 vs. 13.3%, p= 0.140). TRPN was associated with a more estimated blood loss (50 vs. 40 ml, p = 0.004). There were no significant differences in pathologic variables, rate of eGFR decline for postoperative 12-month (9.0 vs. 7.1%, p = 0.449) functional follow-up. Multivariate analysis identified that only RENAL score (odd ratio: 0.641; 95% confidence interval: 0.455-0.904; p = 0.011) was independently associated with the pentafecta achievement. Conclusions: For completely upper pole renal masses, both TRPN and RRPN have good and comparable results. Both surgical approaches remain viable options in the treatment of these cases.